Advances of 2D MoS2 for High-Energy Lithium Metal Batteries - Cha, Eunho; Kim, Do Kyung; Choi, Wonbong (Frontiers in Energy Research, 2021)
Often touted as the most promising next-generation energy storage systems, lithium (Li) metal batteries have drawn extensive interest due to their energy densities beyond those of Li-ion batteries. The use of Li metal, however, presents a major hurdle since it is susceptible to Li dendrite growths, corrosive interfacial reactions, and uncontrolled volume changes. Li-metal protection is an important issue in overcoming those challenges. In particular, studies have shown that molybdenum disulfide (MoS2) can significantly improve the performance and safety of Li metal batteries when used as a protective coating for anodes, separator modification, and stable interfacial layer between solid-electrolytes and Li metal. Herein, we review the successful implementation of MoS2 for improved Li metal batteries including those of the liquid-type and the solid-state cells. We also provide opportunities and prospects of MoS2 applications for the safe and practical Li metal batteries.